Levetiracetam vs. phenobarbitone in neonatal seizures - a randomised controlled trial at a tertiary care hospital in Southern Rajasthan - Das, Dipu; Jain, Bhupesh; Athreyi R., Nehal; K. G., Hrishikesh; Meena, Archana (International Journal of Contemporary Pediatrics, 2025)
Background: Neonatal seizures, most commonly due to hypoxic-ischemic encephalopathy (HIE), represent a medical emergency with substantial morbidity. While phenobarbitone (PB) remains the first-line antiepileptic, its efficacy varies and adverse effects are frequent. Levetiracetam (LEV) may offer a safer and equally effective alternative. Methods: In this randomized controlled trial conducted at RNT Medical College NICU, Udaipur, 120 EEG-confirmed neonatal seizure cases were randomized equally to receive either LEV or PB. Seizure control within 24 hours without switching was the primary outcome; secondary outcomes included drug switching, adverse events, discharge rate and mortality. Results: Baseline characteristics were well-matched between groups. Initial seizure control was achieved in 81.6% of the LEV group and 71.6% of the PB group (p=0.195). After switching, seizure control rates significantly favored LEV over PB (96.7% vs 86.7%, p=0.048). Adverse events occurred in 11.7% of neonates receiving LEV versus 23.3% with PB (p=0.036). No significant difference was observed in mortality or discharge rates between the two groups. Conclusions: Levetiracetam demonstrated a comparable efficacy to phenobarbitone in neonatal seizure control, with a significantly better safety profile and higher effectiveness after drug switching. LEV shows promise as a preferable first-line or adjunctive therapy for neonatal seizures.